The wild one [large type] - Petrie, Nicholas (Petrie, Nicholas. Peter Ash novel., 2020)
"Losing ground in his fight against post-traumatic claustrophobia, war veteran Peter Ash has no intention of getting on an airplane--until a grieving woman asks Peter to find her eight-year-old grandson. The woman's daughter has been murdered. Erik, the dead daughter's husband, is the sole suspect, and he has taken his young son and fled to Iceland for the protection of Erik's lawless family. Finding the boy becomes more complicated when Peter is met at the airport by a man from the United States Embassy. For reasons both unknown and unofficial, it seems that Peter's own government doesn't want him in Iceland. The police give Peter two days of sightseeing in Reykjavik before he must report back for the first available seat home. . . and when they realize Peter isn't going home until he accomplishes his mission, they start hunting him, too. From the northernmost European capital to a rustbound fishing vessel to a remote farm a stone's throw from the arctic, Peter must confront his growing PTSD and the most powerful Icelandic snowstorm in a generation to find a killer, save an eight-year-old boy, and keep himself out of an Icelandic prison--or a cold Icelandic grave"--